P618 Pre-operative oral enteral nutritional optimisation for Crohn's disease: A retrospective UK tertiary IBD centre cohort study. (21st January 2022) - Meade, S; Patel, K V; Luber, R P; O'Hanlon, D; Caracostea, A; Pavlidis, P; Honap, S; Anandarajah, C; Griffin, N; Zeki, S; Ray, S; Mawdsley, J; et al.
Abstract: Background: Low quality evidence suggests that pre-operative exclusive enteral nutrition (E/EN) can improve post-operative outcomes in patients with small bowel Crohn's disease (CD). It is not standard practice in most centres. We aimed to test the hypothesis that pre-operative EN in patients undergoing surgery for CD is associated with improved post-operative outcome. Methods: We performed a single-centre retrospective observational study comparing surgical outcomes in patients receiving 2 weeks pre-operative EN with those who received no nutritional optimisation. Consecutive adult patients undergoing ileal or ileocolonic resection for CD from 2008–2020 were included. The primary end-point was post-operative complications <30-days. Secondary end-points included specific surgical complications, unplanned stoma formation, length of stay, length of bowel resected and biochemical/anthropometric changes. Results: 302 surgeries were included (Fig 1) comprising 104 without nutritional optimisation and 198 optimised cases. EN was delivered orally in all patients not requiring PN. Patients were optimised for median 59 (42–80) days. The optimised cohort were younger at operation and diagnosis, with an increased frequency of penetrating disease, and exposure to antibiotics or biologics. They were more likely to undergo laparoscopic surgery and had favourable outcomes on multivariable analysis (MVA): all complications [OR 0.35; 0.17–0.72, p=0.004], surgical complications [OR 0.39; 95% CI 0.18–0.85, p=0.02], non-surgical complications [OR 0.29 95% CI 0.11–0.77, p=0.01] and infective complications [OR 0.30; 95% CI 0.13–0.69, p=0.005]). There were fewer grade 1 and 2 complications in the optimised cohort (6/198 grade 1 [3.0%] vs 13/104 [12.5%], p=0.001 and 27/198 grade 2 [13.6%] vs 25/104 [24.0%], p=0.02). Rates of unplanned stoma formation, length of stay and length of bowel resected were similar. Nutritional optimisation was associated with an increase in serum albumin (p<0.001) and reduction in serum C-reactive protein (CRP, p<0.001). Optimised patients had a significantly lower serum CRP pre-operatively compared to the non-optimised cohort (4.0 [1.0–13.0] mg/L vs 8.0 [4.0–35.0] mg/L, p<0.001). Poor baseline biochemical parameters (low albumin [p<0.001], low haemoglobin [p=0.04] and high CRP [p=0.02]), and low body mass index (p=0.003) were associated with EN failure. Low baseline serum albumin was the only predictor of EN failure on MVA (p=0.02). In the highest risk group (albumin<30g/L) there was still a 27.3% rate of treatment success (Fig 2). Conclusion: Oral EEN was well tolerated and associated with a reduction in 30-day post-operative complications. Prospective randomised controlled trials are required to confirm these findings.